An Experimental Study On Heat Transfer And Friction Factor Of AL2O3 Nanofluid - L. Syam, Sundar; K. V., Sharma (Faculty Mechanical Engineering, UMP, 2011)
This paper reports experimental investigations of fully developed laminar convective heat transfer and friction factor characteristics of different volume concentrations of Al2O3 nanofluid in a plain tube, fitted with different twist ratios of twisted tape inserts. Experiments are conducted with water and nanofluid in the range of 700  Re  2200, particle volume concentration of 0   0.5%, and twisted tape twist ratios of 0  H / D 15. The heat transfer coefficient of the nanofluid is high compared with water, and further enhancement of heat transfer is observed with the twisted tape inserts. Pressure drop is slightly increased with the inserts, but is comparatively negligible. A generalized regression equation is developed based on the experimental data for the estimation of the Nusselt number and friction factor for water and nanofluid in a plain tube with twisted tape inserts.